In-vitro scavenging activity and acute toxicity study of methanol leaves extract and fractions of Lophira lanceolata Tiegh. Ex Keay (Ochnaceae) in rats. - Jean-Baptiste N. Oussou; Isaac J. Asiedu-Gyekye; Adou F. Yapo; Benoit Banga N’guessan; Patrick Amoateng; Leandre K Kouakou; Isaac K Asante; Etienne E Ehile (International Journal of Phytomedicine, 2016)
The present study aims at comparing in-vitro scavenging activities of methanol extract and fractions of Lophira lanceolata leaves, and also to study the oral acute toxicity of the ethyl acetate fraction. Petroleum ether, dichloromethane, ethyl acetate, butanol and water fractions were prepared from the methanol extract of the plant. The scavenging activity of DPPH (2, 2-Diphenyl-1-picrylhydrazyl), the total phenolic (TPC) and total flavonoid (TFC) contents of the extract and fractions were determined by spectrophotometrical methods using gallic acid (GA) and quercetin (Qu) as reference antioxidant. The fifty percent inhibitory concentration (IC50), fifty percent effective concentration (EC50) and the antiradical power (ARP) were determined for all extract and fractions. An acute toxicity study using a single oral dose of 5000 mg/kg of the ethyl acetate fraction of the plant was conducted in female Albino rats following the OECD (420) Guidelines. Blood samples were collected for hematological and biochemical analysis. Histopathological examinations of the heart, kidney and liver were performed. The results showed that the ethyl acetate fraction of L. lanceolata had the highest free radical scavenging activity of DPPH (IC50=1,43; EC50= 0.07 and ARP = 14,28) and also contain the highest amount of total phenols (14,4±0,02 mg of GA equivalent/g of plant fraction) and total flavonoids (93,3±0,04 mg of Qu equivalent/g of plant fraction) as compared to other fractions and ascorbic acid (IC50=5,82; EC50= 3.44; ARP=3,44). The hematological parameters and the lipid profile didn’t show any major change compared to the control group. However, a significant increase of aspartate aminotransferase (AST, p<0.001) and alanine aminotransferase (ALT, p<0.001) showed that the ethyl acetate fraction of the methanol extract of L. lanceolata leaves might not totally be safe for consumption, in the conditions of our experiment.